Pengaruh Jus Tomat Terhadap Tekanan Darah Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Passo Kecamatan Baguala Kota Ambon Provinsi Maluku: The Effect of Tomato Juice on Blood Pressure in Hypertension Sufferers in the Working Area of Passo Health Center, Baguala District, Ambon City, Maluku Province - Laturette, Winny Valensia (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Hypertension is a public health care that often occurs in the world and also in Indonesia or developing countries. Hypertension is also known as The Silent killer because the sufferer does not know whether he has Hypertension or not. Increased blood pressure or hypertension is caused by a chronic increase in blood pressure that occurs in the blood vessels. And if it is continuously left unchecked it will cause dysfunction in other organs, one of which is the heart and kidneys. In dealing with the problem of Hypertension they often treat Hypertension with pharmacological treatment or treatment with drugs compared to non-pharmacological treatment or without drugs. The purpose of this study was to determine the effect of tomato juice on blood pressure in Hypertensive patients.  Methods: This study uses descriptive research with experimental research methods using a quasi-experimental design. The population in this study was male and 35 females. The sample in this study was 30 respondents who were hypertension sufferers. Sampling technique Based on the existing population; the determination of this study used purposive sampling. The data collection technique used in this study is to use observation sheets. Data analysis using paired t-test. Results: The results of the blood pressure study before being given tomato juice, changes in mild blood pressure were 11 people (36.7%), moderate blood pressure was 9 people (30.0%), and severe blood pressure was 10 people (33.3%). Blood pressure after being given tomato juice changes in normal blood pressure by 11 people (36.7%) mild by 18 people (60.0%) and moderate blood pressure by 1 person (3.3%). Results The statistical test results of the paired T-test for the effect of tomato juice on blood pressure in hypertensive patients obtained a p-value of 0,000 (p < 0,05). Discussion: Blood pressure in hypertensive patients before being given tomato juice in the work area of ​​the Passo Health Center, Baguala District, Ambon City, Maluku Province, almost all experienced hypertension or more than normal limits. Blood pressure in hypertensive patients after being given tomato juice in the Work Area of ​​the Passo Health Center, Baguala District, Ambon City, Maluku Province, almost all respondents experienced a decrease. There is an effect of tomato juice on reducing hypertension in hypertensive patients in the Work Area of ​​the Passo Health Center, Baguala District, Ambon City.